The National Research Library Alliance: A Federal Consortium Formed to Provide Inter-Agency Access to Scientific Information - Laurie E. Stackpole; Roderick D. Atkinson (Issues in Science and Technology Librarianship)
This article outlines the circumstances that led to the formation in the Spring of 1997 of the National Research Library Alliance (NRLA), a consortium of federal libraries. It discusses some of the issues that face organizations when they attempt to act collectively and the need for vendors and libraries to work cooperatively to solve the inherent problems associated with a consortium model. The NRLA's first joint procurement, a license to mount one of the Institute of Scientific Information's "Web of Science" databases, was finalized in July 1997. This procurement, which provides some 5,000 researchers at four institutions with web access to Science Citation Index Expanded, is used throughout the article to illustrate some typical problems that arise when diverse institutions attempt to work in unison, as well as to illustrate the benefits that result from forming partnerships to license critical information resources.